Hyperbaric Oxygen Therapy for Central Retinal Artery Occlusion: Patient Selection and Perspectives - Celebi ARC (Dove Medical Press, 2021)
Ali Riza Cenk Celebi Atakent Education and Research Hospital, Department of Ophthalmology, Acibadem University School of Medicine, Istanbul, TurkeyCorrespondence: Ali Riza Cenk CelebiAtakent Education and Research Hospital, Department of Ophthalmology, Acibadem University School of Medicine, Istanbul, 34303, TurkeyTel +90 212 404 40 84Email arcenkcelebi@gmail.com; cenk.celebi@acibadem.edu.trAbstract: The central retinal artery occlusion (CRAO) is a rare ophthalmological emergency that can occur in the eye. CRAO can affect persons of any age, however it is most common in people over the age of 60. CRAO is associated with a number of risk factors, including giant cell arteritis, carotid artery atherosclerosis, cardiogenic emboli, hypertension, smoking, diabetes, and thromboembolic disease. The chance of each of these etiologies being present is assessed during the course of the investigation. Hyperbaric oxygen treatment (HBOT) is classified by the American Heart Association for CRAO at level IIb. In accordance with that, HBOT might be considered for the treatment of such a severe condition. HBOT can maintain retinal oxygenation during ischemic events by allowing oxygen to diffuse through choroidal capillaries that have been exposed to elevated partial pressures of oxygen. As a result, ischemia-related damage is reversed if applied within proper time frame. The amount of time that has passed prior to initiation of HBOT is considered to be the most critical factor in determining the best visual prognosis. According to the Undersea and Hyperbaric Medical Society, patients who are identified with CRAO after the onset of symptoms should be evaluated for HBOT within 24 hours. HBOT has the advantage of having a low risk profile, and it can be utilized to improve visual outcomes in proper patients.Keywords: hyperbaric oxygen therapy, HBOT, central retinal artery occlusion, CRAO